2017
DOI: 10.1016/j.cub.2017.08.033
|View full text |Cite
|
Sign up to set email alerts
|

BubR1 Promotes Bub3-Dependent APC/C Inhibition during Spindle Assembly Checkpoint Signaling

Abstract: SummaryThe spindle assembly checkpoint (SAC) prevents premature sister chromatid separation during mitosis. Phosphorylation of unattached kinetochores by the Mps1 kinase promotes recruitment of SAC machinery that catalyzes assembly of the SAC effector mitotic checkpoint complex (MCC). The SAC protein Bub3 is a phospho-amino acid adaptor that forms structurally related stable complexes with functionally distinct paralogs named Bub1 and BubR1. A short motif (“loop”) of Bub1, but not the equivalent loop of BubR1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 98 publications
3
38
0
Order By: Relevance
“…Previously, we have reported that the BUBR1/BUB3 and BUB1/BUB3 complexes interact directly and that this interaction is responsible for kinetochore recruitment of BUBR1/BUB3 to phosphorylated MELT (Met-Glu-Leu-Thr) motifs on the kinetochore receptor KNL1 ( 68 , 73 , 74 ). The interaction of BUBR1/BUB3 and BUB1/BUB3 probably reflects the ancient homodimerization of a singleton that preceded the duplication of the BUBR1 and BUB1 paralogs, because it involves equivalent structural domains in BUB1 and BUBR1, comprising the BUB3-binding domain and a subsequent predicted helical domain ( 73 , 74 ). We asked whether the interaction of BUBR1/BUB3 and BUB1/BUB3 was compatible with their respective interactions with CENP-E and CENP-F, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have reported that the BUBR1/BUB3 and BUB1/BUB3 complexes interact directly and that this interaction is responsible for kinetochore recruitment of BUBR1/BUB3 to phosphorylated MELT (Met-Glu-Leu-Thr) motifs on the kinetochore receptor KNL1 ( 68 , 73 , 74 ). The interaction of BUBR1/BUB3 and BUB1/BUB3 probably reflects the ancient homodimerization of a singleton that preceded the duplication of the BUBR1 and BUB1 paralogs, because it involves equivalent structural domains in BUB1 and BUBR1, comprising the BUB3-binding domain and a subsequent predicted helical domain ( 73 , 74 ). We asked whether the interaction of BUBR1/BUB3 and BUB1/BUB3 was compatible with their respective interactions with CENP-E and CENP-F, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, we characterized in molecular detail how sequence divergence impacted the protein interaction potential of the human BUB1 and BUBR1 paralogs ( 73 , 74 ). We described a molecular mechanism that explains how BUB1, through an interaction with a phospho-amino acid adaptor named BUB3, can interact with kinetochores and promote the recruitment of BUBR1 via a pseudo-dimeric interface ( 73 75 ). In view of these previous studies, here we have dissected the molecular basis of the interactions of BUBR1 and BUB1 with CENP-E and CENP-F. We provide strong evidence for the sub-functionalization of these paralogous protein pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on human Bub1 and BubR1, including our own work, demonstrated that these paralogs sub-functionalized in various ways, including 1) the selective inactivation of the kinase domain in BubR1; 2) the development of phospho-aminoacid recognition modules that contribute to the ability of Bub3 to recognize distinct substrates; and 3) the interaction with distinct binding partners that subtends to distinct functions in chromosome alignment and mitotic checkpoint signaling (Figure 7) (Overlack et al, 2017; Overlack et al, 2015; Primorac et al, 2013; Suijkerbuijk et al, 2012; van Hooff et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…In our previous studies, we characterized in molecular detail how sequence divergence impacted the protein interaction potential of the human Bub1 and BubR1 paralogs (Overlack et al, 2017; Overlack et al, 2015). We described a molecular mechanism that explains how Bub1, through an interaction with a phospho-aminoacid adaptor named Bub3, can interact with kinetochores and promote the recruitment of BubR1 via a pseudo-dimeric interface (Overlack et al, 2017; Overlack et al, 2015; Primorac et al, 2013). In view of these previous studies, here we have dissected the molecular basis of the interactions of BubR1 and Bub1 with CENP-E and CENP-F. We provide strong evidence for the sub-functionalization of these paralogous protein pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Bub1 is a kinetochore-associated protein kinase which regulates the Spindle Assembly Checkpoint (SAC) and kinetochore-microtubule attachment (Elowe, 2011 ). Cdc20, Mad1/2 and Histone H2A appear as major substrates, while Bub1 also plays a scaffolding role at kinetochores to recruit the pseudokinase BubR1 (Tang et al, 2004 ; Yamagishi et al, 2010 ; Suijkerbuijk et al, 2012 ; Overlack et al, 2015 , 2017 ; Jia et al, 2016 ). Structural characterization of Bub1 kinase domain reveals the role of its N-terminal extension in positioning the C-helix and stabilizing the conformation of the activation segment (Lin et al, 2014 ) (Figure 2 ).…”
Section: Mechanisms Of Kinase Activationmentioning
confidence: 99%